Arsenite induces ferroptosis in the neuronal cells via activation of ferritinophagy. (May 2021) - Xiao, Junting; Zhang, Shanshan; Tu, Baijie; Jiang, Xuejun; Cheng, Shuqun; Tang, Qianghu; Zhang, Jun; Qin, Xia; Wang, Bin; Zou, Zhen; Chen, Chengzhi
Abstract: Ferroptosis is a novel form of cell death that involves in the pathophysiological process of diverse brain diseases. However, how arsenite induces ferroptosis in the neuronal cells remains unsolved. In this study, by using in vitro and in vivo models, we demonstrated that arsenite was able to trigger ferroptosis in the neuronal cells. Exposure of arsenite for 6 months at 0.5, 5 and 50 mg/L arsenite via drinking water significantly reduced the number of neurons and caused the pathological changes in the mitochondria of hippocampus. Treatment of arsenite elevated the contents of lipid peroxidation products, disrupted the iron homeostasis, altered the expressions of ferroptosis-related proteins in the hippocampus and PC-12 cells. The results also showed that arsenite significantly decreased the expressions of ferritin and NCOA4, but sharply enhanced the level of autophagy marker LC3B, suggesting the activation of ferritinophagy by arsenite. Co-treatment of arsenite with ferroptosis inhibitor ferrostatin-1, or autophagy inhibitors 3-MA and BafA1, all remarkably attenuated the cytotoxic effects of arsenite. These findings not only present a novel mechanism that arsenite triggers ferroptosis in the neuronal cells via activation of ferritinophagy, but also indicate that regulating ferritinophagy to control iron level may provide a clue for prevention against arsenite neurotoxicity. Graphical abstract: Image 1 Highlights: Arsenite induces ferroptosis in the hippocampus and PC-12 cells. Inhibition of ferroptosis attenuates arsenite-induced neuronal cell death. Arsenite disrupts iron homeostasis in the hippocampus and PC-12 cells. Arsenite triggers ferroptosis in neuronal cells via activation of ferritinophagy.